Management of pain in patients with bone metastases - Jing, Doudou; Zhao, Qian; Zhao, Yibo; Lu, Xiangdong; Feng, Yi; Zhao, Bin; Zhao, Xiaofeng (Frontiers in Oncology, 2023)
Cancer-induced bone pain (CIBP) has a considerable impact on patients’ quality of life as well as physical and mental health. At present, patients with CIBP are managed according to the three-step analgesic therapy algorithm proposed by the World Health Organization. Opioids are commonly used as the first-line treatment for moderate-to-severe cancer pain but are limited due to addiction, nausea, vomiting and other gastrointestinal side effects. Moreover, opioids have a limited analgesic effect in some patients. In order to optimize the management of CIBP, we must first identify the underlying mechanisms. In some patients, surgery, or surgery combined with radiotherapy or radiofrequency ablation is the first step in the management of CIBP. Various clinical studies have shown that anti-nerve growth factor (NGF) antibodies, bisphosphonates, or RANKL inhibitors can reduce the incidence and improve the management of cancer pain. Herein, we review the mechanisms of cancer pain and potential therapeutic strategies to provide insights for optimizing the management of CIBP.